2019
DOI: 10.1128/mra.00595-19
|View full text |Cite
|
Sign up to set email alerts
|

Genome Sequence of Lipopeptide- and Antioxidant-Producing Strain Bacillus velezensis NWUMFkBS10.5

Abstract: Candidate biocontrol agent Bacillus velezensis NWUMFkBS10.5 possesses unique genomic characteristics revealed by antiSMASH analysis and in vitro metabolomic elucidation. Besides its capability to produce antimicrobial lipopeptides, further in silico genome profiling predicted the presence of metabolic pathways for synthesizing antioxidants like lampranthin-2, miraxanthin V, and 2-decarboxybetanidin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Whilst antagonist PS9.1 possesses some plant-growth-promoting and biocontrol compounds, rhamnolipids, pyoverdine, and rhizomide [ 22 , 32 ], the antagonist NWUMFkBS10.5 performed significantly ( p = 0.05) better than PS9.1 in all the treatments. This could be attributed to the action of its multiple plant-growth-promoting and biocontrol biosynthetic compounds, macrolactin, bacillibactin, mersacidin, bacilysin, surfactin, difficidin, iturin, and fengycin [ 21 , 33 ]. A large number of the Bacillus and Pseudomonas spp.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whilst antagonist PS9.1 possesses some plant-growth-promoting and biocontrol compounds, rhamnolipids, pyoverdine, and rhizomide [ 22 , 32 ], the antagonist NWUMFkBS10.5 performed significantly ( p = 0.05) better than PS9.1 in all the treatments. This could be attributed to the action of its multiple plant-growth-promoting and biocontrol biosynthetic compounds, macrolactin, bacillibactin, mersacidin, bacilysin, surfactin, difficidin, iturin, and fengycin [ 21 , 33 ]. A large number of the Bacillus and Pseudomonas spp.…”
Section: Discussionmentioning
confidence: 99%
“…fulva PS9.1 and B . velezensis NWUMFkBS10.5, were previously isolated from the maize rhizosphere, identified based on the 16S rDNA gene sequence analysis (accession numbers MF098600 and KX353617.1), and analyzed by genome sequencing [ 21 , 22 , 32 , 33 ]. The Fg pathogen was provided as a gift.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, Adeniji and Babalola ( 2019 ) revealed that an in silico analysis of the strain genome by antiSMASH could permit to predict which antioxidant molecules could potentially be produced by a strain. In their study, they showed that Bacillus valezensis NWUMFkBS10.5 was potentially able to produce antioxidant molecules such as lampranthin-2, miraxanthin V, and 2-decarboxybetanidin.…”
Section: Introductionmentioning
confidence: 99%